Peran Teknologi dalam Optimalisasi Pengumpulan dan Distribusi Zakat Dan Wakaf - Ali, Sapri; Azzafa Nur Jadidah (El-Faqih : Jurnal Pemikiran dan Hukum Islam, 2024)
The role of technology in optimizing the collection and distribution of zakat and waqf has become an increasingly relevant research subject in managing Islamic charitable funds. Information and communication technology is crucial in increasing efficiency, transparency, and accountability in the zakat and waqf management process. As a qualitative research, this article investigates an in-depth understanding of various technological innovation phenomena applied to this problem, including using digital platforms, blockchain, and artificial intelligence to overcome traditional challenges in distributing charitable funds. Using a deductive approach, this research reviews the positive impact of technology adoption on increasing community participation, updating the fund collection system, and expanding the reach and operational efficiency of zakat and waqf institutions. Through this analysis, this journal aims to provide in-depth and relevant insights for practitioners, academics, and policymakers in utilizing the potential of technology to strengthen zakat and waqf management in the digital era.